The Influence of Village Fund Policy Implementation, Communuty Participation and Organizational Performance on the Effectiveness of Village Development in Tulang Bawang District of Lampung Province - Dedy Palwadi; Fernandes Simangunsong; Sampara Lukman; Agus Fatoni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of the study These are (1) to discuss the effect of implementing the village fund policy on the effectiveness of village development; (2) To discuss the effect of community participation on the effectiveness of village development; (3) To discuss organizational performance on the effectiveness of village development; (4) To discuss the effect of implementing village fund policies, community participation and organizational performance together on the effectiveness of development. The research method used in this research is quantitative research. The source of data to be studied is primary data. Primary data is data obtained directly from the source or place of research carried out directly. Primary data in this study were obtained through questionnaires distributed to respondents. The relationship between the implementation of the Village Fund Policy and the Effectiveness of Village Development is significant with a t-count value of 3.320 and a t-table value of 1.653 with a significant value of 0.01 or <0.05. The implementation of the Village Fund Policy affects the Effectiveness of Village Development. The relationship between Community Participation and Village Development Effectiveness is significant with a t-count value of 4.098 and a t-table value of 1.653 with a significant value of 0.000 or <0.05. Community Participation affects the Effectiveness of Village Development. The relationship between Organizational Performance and Effectiveness of Village Development is significant with a t-count value of 3.658 and a t-table value of 1.653 with a significant value of 0.000 or <0.05. Organizational Performance affects the Effectiveness of Village Development. The implementation of the Village Fund Policy, Community Participation and Organizational Performance together has an influence on the Effectiveness of Village Development with the value of Sig. < 0.05. The effectiveness of village development really needs the synergy of 4A, namely APBDes, Regency/City APBD, Provincial APBD and APBN to realize optimal Village Development and utilize information technology by integrating planning and budgeting starting from the village level to the central level.